2008
DOI: 10.1002/cphc.200800450
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopy of a Wilkinson Catalyst in a Room‐Temperature Ionic Liquid

Abstract: Homogeneous catalysis in room‐temperature ionic liquids (ILs) constitutes a most interesting field of research with high potential in technical applications. As concerns the hydrogenation of unsaturated hydrocarbons, Wilkinson’s compound RhCl(PPh3)3 represents a catalyst that provides high selectivity and activity. Herein, we demonstrate the application of infrared spectroscopy to the quantitative analysis of the Wilkinson catalyst in the IL 1‐ethyl‐3‐methylimidazolium acetate ([EMIM][OAc]). Our study demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…MCC/EmimAc/water systems with high concentration, ranging from 6 to 16 wt %, were prepared by adding different amount of MCC (by drying weight) to the mixed solvents, and dissolving them by stirring vigorously at 80 °C for 5 h in closed containers to avoid any change in water content. These concentrations were chosen because it has been reported that cellulose/IL solutions become optically anisotropic at high concentrations (near 10 wt %), which can greatly influence spinning process, structure, and mechanical properties of the cellulose fiber . In addition, a sample without water was prepared under the same conditions.…”
Section: Methodsmentioning
confidence: 99%
“…MCC/EmimAc/water systems with high concentration, ranging from 6 to 16 wt %, were prepared by adding different amount of MCC (by drying weight) to the mixed solvents, and dissolving them by stirring vigorously at 80 °C for 5 h in closed containers to avoid any change in water content. These concentrations were chosen because it has been reported that cellulose/IL solutions become optically anisotropic at high concentrations (near 10 wt %), which can greatly influence spinning process, structure, and mechanical properties of the cellulose fiber . In addition, a sample without water was prepared under the same conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed analysis of the fingerprint region revealed that the ring bending mode of the imidazolium moiety shows a frequency shift as a function of the catalyst concentration. Thus, a hydrogen-bond between the imidazolium cation and the rhodium complex was supposed [43].…”
Section: Platinum Metal Complexes Identified As Catalytic Precursors/mentioning
confidence: 99%
“…However, there are efforts going on to make vibrational spectroscopy a tool for more complex systems. For instance, IR spectroscopy has been employed for quantitative measurements of carbohydrates or a Wilkinson catalyst dissolved in ionic liquids [41,42]. In the case of the catalyst experiments, the spectra revealed a red-shift of imidazolium ring bending mode with increasing catalyst concentration.…”
Section: Potential Challenges and Future Applicationsmentioning
confidence: 99%